Microbial preparation with lactic acid activity (lab) as biological accelerant in the fermentation process to feed cattle - Borrás-Sandoval, Luis Miguel; Valiño-Cabrera, Elaine Cristina; Rodríguez-Molano, Carlos Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The objective of this study was to develop a microbial preparation, starting from an elaborated yogurt, based on a lactic acid bacteria (BAL) culture of medium and fast acidification, Lactobacillus de/brueckii ssp bu/garicus and Streptococcust hermophilus, from a commercial lyophilized culture (Liofast Y452B, SACCO ®). For the pH microbial preparation, an ANOVA analysis was carried out, by dividing the fermentation in 6 time intervals (O, 6, i2, 24, 36 and 48 hours) with three replicates. The inoculum preparation started from the elaboration of the yogurt, which was prepared with whole cow’s milk, heated to 45 °C, and inoculated with lactic acid bacteria culture. The final product showed a pH of 4.63 at 48 h, (p<0.0001); this product controlled the bacterial pathogens growth, and allowed a lactic acid bacteria final growth of 99x106 UFC/mL, to be used as microbial additive and as biological accelerator in fermentation processes, and possibly as a probiotic use for animal feed.